1 μJ nanosecond low-coherent laser source with precise temporal shaping and spectral control. (February 2020) - Rao, Daxing; Gao, Yanqi; Cui, Yong; Ji, Lailin; Zhao, Xiaohui; Liu, Jia; Liu, Dong; Li, Fujian; Shan, Chong; Shi, Haitao; Liu, Jiani; Feng, Wei; et al.
Highlights: Low-coherent pulse with precise temporal shaping and spectral control. μJ-level instantaneous broadband pulse of time-spectrum independent. Coherence time is 123 fs, much shorter than pulse duration. Output instability less than 1% rms and 8% peak-to-valley over 4 h. Abstract: A μJ-level low-coherent pulse with dynamic and precise temporal shaping and spectral control is demonstrated. Low-coherent light delivered by a superluminescent diode is precisely shaped through a wave guide amplitude modulator driven by an arbitrary waveform generator. Utilizing a three-stage axial-alternating polarization-maintaining single-mode fiber amplifier, μJ-level low-coherent pulses with 3 ns durations and 20 nm instantaneous bandwidths at a 1 kHz repetition rate are obtained. In addition, a spectral control unit is used to adjust the spectrum shape. As a result, near flat-top, saddle-type, or other required special spectra can be produced. The low temporal coherence characteristics and output stability are characterized experimentally.